Hiring preferences of special libraries in Makati - Dineros, Jennifer L. (2007)
Among the resources that a library should spend on is a competitive staff. A competitive staff could maximize the potential of an institution whereas an uncompetitive staff could cause the elimination an established organization. It is necessary therefor to examine the hiring preferences of libraries.